Rivaroxaban in secondary prevention of cardioembolic stroke: standards and abnormal situations - A.V. Fonyakin; L.A. Geraskina (Неврология, нейропсихиатрия, психосоматика)
Possibilities of antithrombotic therapy in prevention of cardioembolic stroke (CES) in patients with nonvalvular atrial fibrillation (AF) were significantly broadened after new oral anticoagulants (NOC) have been designed and launched into clinical practice (rivaroxaban being one of these agents). In real-life clinical practice, nonvalvular AF can be combined with various cardiovascular pathologies in patients who have had CES, thus giving rise to situations when there are no specific recommendations for NOC. The article analyzes the most common comorbid clinical situation in vascular neurology and evaluates the potential of rivaroxaban as an alternative to warfarin. Rivaroxaban is shown to be a promising drug for widespread use in angio-neurological practice for treating combined cardiovascular pathology.